Reduksi Waste untuk Meningkatkan Produktivitas pada Proses Produksi Bracket Roulet Gordyn Menggunakan Pendekatan Lean Manufacturing - Arief Rahman Somantri (Jurnal Riset Teknik Industri, 2021)
Abstract. CV. UM is a manufacturing industry that produces Bracket Roulet Gordyn. In running its business, CV. UM often experience delays in fulfilling customer requests. Factors that cause this problem is because of the amount of waste activity, thus making production lead time become long and productivity levels decrease. When productivity decreases, it affects the speed of customer demand fulfillment. Therefore, Lean Manufacturing approach can be used as an effort to reduce waste. This study aims to reduce waste so that the productivity of CV. UM is increasing. Based on the results of waste identification using Value Stream Mapping (VSM), and 7 waste questionnaire, it is known that there are 4 types of dominant waste that inhibit the production flow, namely Excessive Transportation, Waiting, Unnecessary Motion, and Unnecessary Inventory. To solve this problem, improvement efforts are proposed by applying the design of tools in the form of Roll Conveyor, pulley systems, containers, and crocks, application of the concept of 5S, production layout redesign, the addition of facilities that support the production process in the form of Trolley Pallet Jack and Wooden Pallet, and the application of Lean Thinking. If improvement efforts to reduce waste are implemented, production lead time is expected to be reduced by 19% from 20.007,04 seconds to 16.175,04 seconds. The decrease can increase Process Cycle Efficiency (PCE) or company productivity = increased by 13,43% from 52,47% to 66,17%. Abstrak. CV. UM merupakan industri manufaktur yang memproduksi Bracket Roulet Gordyn. Dalam menjalankan bisnisnya, CV. UM sering mengalami keterlambatan dalam memenuhi permintaan pelanggan. Faktor yang menyebabkan hal tersebut yaitu banyaknya aktivitas pemborosan (waste), sehingga membuat production lead time menjadi panjang dan tingkat produktivitas menurun. Ketika produktivitas menurun, maka akan mempengaruhi kecepatan pemenuhan permintaan pelanggan. Oleh karena itu, pendekataan Lean Manufacturing dapat dimanfaatkan sebagai upaya untuk mereduksi waste. Penelitian ini bertujuan untuk mereduksi waste agar produktivitas CV. UM meningkat. Berdasarkan hasil identifikasi waste menggunakan Value Stream Mapping (VSM) dan kuesioner 7 waste, diketahui bahwa terdapat 4 jenis waste dominan yang menghambat aliran produksi yaitu Excessive Transportation, Waiting, Unnecessary Motion, dan Unnecessary Inventory. Untuk mengatasi masalah tersebut, diusulkan upaya perbaikan dengan menerapkan rancangan alat bantu berupa Roll Conveyor, sistem katrol, kontainer, dan wadah, penerapan konsep 5S, perancangan ulang layout produksi, penambahan fasilitas pendukung proses produksi berupa Trolley Pallet Jack beserta Wooden Pallet, dan penerapan Lean Thinking. Apabila upaya perbaikan untuk mereduksi waste diterapkan, diharapkan production lead time berkurang sebesar 19% dari 20.007,04 detik menjadi 16.175,04 detik. Penurunan tersebut dapat meningkatkan Process Cycle Efficiency (PCE) atau produktivitas perusahaan = sebesar 13,43% dari 52,47% menjadi 66,17%.